Synthesis of a novel aminobenzene-containing hemicucurbituril and its fluorescence spectral properties with ions - Zeng, Qingkai; Long, Qiumeng; Lu, Jihong; Wang, Li; You, Yuting; Yuan, Xiaoting; Zhang, Qianjun; Ge, Qingmei; Cong, Hang; Liu, Mao (Beilstein Journal of Organic Chemistry, 2021)
A novel hemicucurbituril-based macrocycle, alternately consisting of amidobenzene and 2-imidazolidione moieties was designed and synthesized. Based on the fragment coupling strategy, nitrobenzene-containing hemicucurbituril was firstly prepared facilely under alkaline environment, and reduction of the nitro groups produced the desired amidobenzene-containing hemicucurbituril. As an original fluorescent chemosensor, it exhibited strong interactions with Fe3+ over other metal cations. The experimental evidence of fluorescence spectra suggested that a 1:1 complex was formed between this macrocycle and Fe3+ with an association constant up to (2.1 ± 0.3) × 104 M−1. Meanwhile, this macrocycle showed no obvious or only slight enhancement of the fluorescence intensity with selected anions.
Keywords: amidobenzene-containing macrocycle; hemicucurbituril; host–guest interaction; macrocycle; modification

(untitled) - Yudin, A. K. (Chem. Sci., 2015)

(untitled) - Jasti, R.; Bhattacharjee, J.; Neaton, J. B.; Bertozzi, C. R. (J. Am. Chem. Soc., 2008)

(untitled) - Omachi, H.; Segawa, Y.; Itami, K. (Acc. Chem. Res., 2012)

(untitled) - Yamago, S.; Kayahara, E.; Iwamoto, T. (Chem. Rec., 2014)

(untitled) - Golder, M. R.; Jasti, R. (Acc. Chem. Res., 2015)

(untitled) - Della Sala, P.; Talotta, C.; De Rosa, M.; Soriente, A.; Geremia, S.; Hickey, N.; Neri, P.; Gaeta, C. (J. Org. Chem., 2019)

(untitled) - Kayahara, E.; Nakano, M.; Sun, L.; Ishida, K.; Yamago, S. (Chem. – Asian J., 2020)

(untitled) - Hermann, M.; Wassy, D.; Esser, B. (Angew. Chem., Int. Ed., 2021)

(untitled) - Ogoshi, T.; Kanai, S.; Fujinami, S.; Yamagishi, T.-a.; Nakamoto, Y. (J. Am. Chem. Soc., 2008)

(untitled) - Cragg, P. J.; Sharma, K. (Chem. Soc. Rev., 2012)

(untitled) - Huang, H.; Liu, L.; Duan, W.; Huang, Y.; Lin, G. (Chin. J. Chem., 2015)

(untitled) - Zhang, R.; Wang, C.; Long, R.; Chen, T.; Yan, C.; Yao, Y. (Front. Chem. (Lausanne, Switz.), 2019)

(untitled) - Lee, E.; Ryu, H.; Ju, H.; Kim, S.; Lee, J.-E.; Jung, J. H.; Kuwahara, S.; Ikeda, M.; Habata, Y.; Lee, S. S. (Chem. – Eur. J., 2019)

(untitled) - Yang, W.; Samanta, K.; Wan, X.; Thikekar, T. U.; Chao, Y.; Li, S.; Du, K.; Xu, J.; Gao, Y.; Zuilhof, H.; Sue, A. C.-H. (Angew. Chem., Int. Ed., 2020)

(untitled) - Gu, M.-D.; Lu, Y.; Wang, M.-X. (Beilstein J. Org. Chem., 2019)

(untitled) - Guo, S.-Y.; Guo, Q.-H.; Tong, S.; Wang, M.-X. (Angew. Chem., Int. Ed., 2020)

(untitled) - Zhuang, S.-Y.; Cheng, Y.; Zhang, Q.; Tong, S.; Wang, M.-X. (Angew. Chem., Int. Ed., 2020)

(untitled) - König, B.; Fonseca, M. H. (Eur. J. Inorg. Chem., 2000)

(untitled) - Wang, M.-X. (Chem. Commun., 2008)

(untitled) - Miyahara, Y.; Goto, K.; Oka, M.; Inazu, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Ogoshi, T.; Kakuta, T.; Yamagishi, T.-a. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ghosh, I.; Nau, W. M. (Adv. Drug Delivery Rev., 2012)

(untitled) - Wei, P.; Sobotta, F. H.; Kellner, C.; Bandelli, D.; Hoeppener, S.; Schubert, S.; Brendel, J. C.; Schubert, U. S. (Polym. Chem., 2020)

(untitled) - Andersen, N. N.; Lisbjerg, M.; Eriksen, K.; Pittelkow, M. (Isr. J. Chem., 2018)

(untitled) - Masson, E.; Ling, X.; Joseph, R.; Kyeremeh-Mensah, L.; Lu, X. (RSC Adv., 2012)

(untitled) - Buschmann, H.-J.; Zielesny, A.; Schollmeyer, E. (J. Inclusion Phenom. Macrocyclic Chem., 2006)

(untitled) - Kaabel, S.; Aav, R. (Isr. J. Chem., 2018)

(untitled) - Svec, J.; Necas, M.; Sindelar, V. (Angew. Chem., Int. Ed., 2010)

(untitled) - Havel, V.; Sadilová, T.; Šindelář, V. (ACS Omega, 2018)

(untitled) - Lizal, T.; Sindelar, V. (Isr. J. Chem., 2018)

(untitled) - Prigorchenko, E.; Öeren, M.; Kaabel, S.; Fomitšenko, M.; Reile, I.; Järving, I.; Tamm, T.; Topić, F.; Rissanen, K.; Aav, R. (Chem. Commun., 2015)

(untitled) - Reany, O.; Mohite, A.; Keinan, E. (Isr. J. Chem., 2018)

(untitled) - Havel, V.; Yawer, M. A.; Sindelar, V. (Chem. Commun., 2015)

(untitled) - Weber, E.; Trepte, J.; Gloe, K.; Piel, M.; Czugler, M.; Kravtsov, V. C.; Simonov, Y. A.; Lipkowski, J.; Ganin, E. V. (J. Chem. Soc., Perkin Trans. 2, 1996)

(untitled) - Prusinowska, N.; Szymkowiak, J.; Kwit, M. (J. Org. Chem., 2018)

(untitled) - Lízal, T.; Šindelář, V. (Beilstein J. Org. Chem., 2019)

(untitled) - Parvari, G.; Annamalai, S.; Borovoi, I.; Chechik, H.; Botoshansky, M.; Pappo, D.; Keinan, E. (Chem. Commun., 2014)

(untitled) - Huang, Y.-H.; Jin, X.-Y.; Yan, S.; Cong, H.; Tao, Z. (ChemistrySelect, 2018)

(untitled) - Huang, Y.-H.; Jin, X.-Y.; Zhao, Y.-Y.; Cong, H.; Tao, Z. (Org. Biomol. Chem., 2018)

(untitled) - Huang, Y.-H.; Ge, Q.-M.; Zhao, Y.-Y.; Cong, H.; Zhao, J.-L.; Tao, Z.; Luo, Q.-Y. (Spectrochim. Acta, Part A, 2019)

(untitled) - Luo, H.; Zhao, Y.-Y.; Jin, X.-Y.; Yang, J.-M.; Cong, H.; Ge, Q.-M.; Sun, L.; Liu, M.; Tao, Z. (Electroanalysis, 2020)

(untitled) - Qiu, F.; Huang, Y.-H.; Ge, Q.; Liu, M.; Cong, H.; Tao, Z. (Spectrochim. Acta, Part A, 2020)

(untitled) - Zhao, Y.-Y.; Li, H.; Ge, Q.-M.; Cong, H.; Liu, M.; Tao, Z.; Zhao, J.-L. (Microchem. J., 2020)

(untitled) - Zhao, Y.-Y.; Luo, H.; Ge, Q.; Liu, M.; Tao, Z.; Cong, H. (Sens. Actuators, B, 2021)

(untitled) - Luo, H.; Li, H.; Ge, Q.; Cong, H.; Tao, Z.; Liu, M. (Microchem. J., 2021)

(untitled) - Chhikara, B. S.; Kumar, N.; Tandon, V.; Mishra, A. K. (Bioorg. Med. Chem., 2005)

(untitled) - Thordarson, P. (Chem. Soc. Rev., 2011)

(untitled) - Song, P.-S.; Chae, Q.; Fujita, M.; Baba, H. (J. Am. Chem. Soc., 1976)